Hadith #2303 - Sunan Abi Dawud - al-Hasan bin Muslim bin Yanaq الحسن بن مسلم بن يناق; Ibrahim bin Tahman إبراهيم بن طهمان; Safiyya bint Shayba bin 'Uthman; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
The tradition mentioned above has also been narrated by Al ‘Umm Athiyah from the Prophet (ﷺ) through a different chain of narrators. The tradition narrated by Yazid bin Harun from Hisham does perfectly correspond to the tradition transmitted by Ibrahim bin Tahman and ‘Abd Allah Al Shami from Hisham. The narrator Al Misma’I reported Yazid as saying “I do not know but that he said “she should not dye herself.” To this the narrator Harun added “She should not wear colored clothes ex
Grade: Sahih

Hadith #2469 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Ma'mar bin Rashid معمر بن راشد; Safiyya bint Shayba bin 'Uthman (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to observe I’tikaf in the mosque and put his head near me through the opening of the apartment, and I would wash his head. Musaddad said: “And I would comb it while I was menstruating.”
Grade: Sahih

Hadith #4031 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; Mus'ab bin Shayba bin Jbyr مصعب بن شيبة بن جبير بن شيبة; Safiyya bint Shayba bin 'Uthman; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who copies any people is one of them.
Grade: Hasan Sahih

Hadith #4099 - Sunan Abi Dawud - Aisha bint Abi Bakr; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Ibrahim bin Mhajr bin Jabir إبراهيم بن مهاجر بن جابر; Safiyya bint Shayba bin 'Uthman; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) cursed mannish women.
Grade: Sahih

Hadith #4100 - Sunan Abi Dawud - Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Safiyya bint Shayba bin 'Uthman; Umm Salamah (Sunan Abi Dawud)
When Surat an-Nur came down, they took the curtains, tore them and made head covers (veils) of them.
Grade: Hasan

Hadith #4992 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Ma'mar bin Rashid معمر بن راشد; Safiyya bint Shayba bin 'Uthman (Sunan Abi Dawud)
The Prophet (ﷺ) said: It is enough falsehood for a man to relate everything he hears. Abu Dawud said: Hafs did not mention Abu Hurairah (in his version). Abu Dawud said: No other transmitter except this old man, that is, ‘Ali b. Hafs al-Mada’ini related the perfect chain of this tradition.
Grade: Sahih